(untitled) (Revista Apotheke, 2017)
This article is the result of a research on teacher training considering theoretical and political productions on the education training, speciﬁcally the Institutional Program of the Initiation to Teaching Grant (PIBID – Programa Institucional de Bolsa de Iniciação à Docência). The guiding questions are: what are the main challenges and perspectives for teaching according to the theoretical productions in evidence? How do the PIBID scholarship students perceive the inﬂuences of the Program in their formation? What are the relationships between the theoretical premises and the effective contribution of PIBID in the training of this students? It is a bibliographical study combined with documentary analysis. From a qualitative approach, the data were discussed considering principles of a content analysis. Among the trends identiﬁed in theoretical productions are: the conception of teaching as a highly complex profession in which teachers deal with human interactions and diverse and adverse situations in which they need to mobilize knowledge, for example, those related to their own experience; the principle of "teacher as protagonist", in which teachers are seen as subjects, authors and mentors of the construction of their professional identity drawn during the initial training process in the exercise of the profession; the relationship between universities and schools with a view towards integrating proposals and training projects. In several respects, there is a certain consonance between the productions about the teacher formation and the experiences of the students on the Program, as it was possible to identify in the reports that it allows a greater articulation between theory and practice; promotes a more in-depth recognition of the school context and, in particular, of the classroom; enables the construction of speciﬁc knowledge for the teaching practice, with increasing autonomy and protagonism.